CHARACTERISTICS OF SCIENTIFIC PAPERS ON RESEARCH OF THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF PUBLIC ADMINISTRATION OF REGIONAL EDUCATION SYSTEM - Postupna O.V., (Pressing Problems of Public Administration, 2016)
The article analyses the scienti c works of Ukrainian scientists on the theoretical and methodologicalfoundations of public administration in regional education system, de nes the authoritativecharacteristics of scienti c achievements as one of the criteria for quality research in the context ofnational interest.